Parallel computational technologies : 11th International Conference, PCT 2017, Kazan, Russia, April 3-7, 2017, Revised selected papers /: 11th International Conference, PCT 2017, Kazan, Russia, April 3-7, 2017, Revised selected papers. (2017) - Unknown
No abstract available